Feed variation and biometrical factors in tilapias (Oreochromis niloticus) exposed to 60Co gamma radiation - Giarola, Rodrigo S. [UNESP]; Borin, Fernando H.R. [UNESP]; Hormaza, Joel M. [UNESP]; Fernandes, Marco A.R. [UNESP]; Ramos, Paulo R.R. [UNESP]; Delicio, Helton C. [UNESP] (My University, 2016)
Ionizing radiation has been widely used for cancer treatment and diagnostic exams in medicine, besides being used in the fields of energy generation and industry. This work aimed to verify the occurrence of biological effects of high doses of gamma radiation using biometric tests in Nile tilapia. 32 fishes where divided into four groups: a control group and three groups irradiated with different values of absorbed dose (20 Gy, 40 Gy and 80 Gy). The fish showed high resistance to the deleterious effects of gamma radiation. Future studies may prove the use of fish for monitoring radiation contaminated environments.